Disseminating alcohol screening and brief intervention at trauma centers: a policy‐relevant cluster randomized effectiveness trial1. (28th February 2014) - Zatzick, Douglas; Donovan, Dennis M.; Jurkovich, Gregory; Gentilello, Larry; Dunn, Chris; Russo, Joan; Wang, Jin; Zatzick, Christopher D.; Love, Jeff; McFadden, Collin; Rivara, Frederick P.
Abstract Background and Aims In 2005 the American College of Surgeons passed a mandate requiring that level I trauma centers have mechanisms to identify and intervene with problem drinkers. The aim of this investigation was to determine if a multi‐level trauma center intervention targeting both providers and patients would lead to higher‐quality alcohol screening and brief intervention (SBI) when compared with trauma center mandate compliance without implementation enhancements. Design Cluster randomized trial in which intervention site (site n = 10, patient n = 409) providers received 1‐day workshop training on evidence‐based motivational interviewing (MI) alcohol interventions and four 30‐minute feedback and coaching sessions; control sites (site n = 10, patient n = 469) implemented the mandate without study team training enhancements. Setting Trauma centers in the United States of America. Participants A total of 878 blood alcohol‐positive in‐patients with and without traumatic brain injury (TBI). Measurements MI skills of providers were assessed with fidelity coded standardized patient interviews. All patients were interviewed at baseline and 6‐ and 12‐months post‐injury with the Alcohol Use Disorders Identification Test (AUDIT). Findings Intervention site providers consistently demonstrated enhanced MI skills compared with control providers. Intervention patients demonstrated an 8% reduction in AUDIT hazardous drinking relative to controls over the course of the year after injury (relative risk = 0.88, 95%, confidence interval = 0.79, 0.98). Intervention patients were more likely to demonstrate improvements in alcohol use problems in the absence of traumatic brain injury (TBI) (P = 0.002). Conclusion Trauma center providers can be trained to deliver higher‐quality alcohol screening and brief intervention (SBI) than untrained providers, which is associated with modest reductions in alcohol use problems, particularly among patients without TBI.